FUNDAMENTOS PARA LA INADMISIBILIDAD DE LA PRUEBA PROHIBIDA Y LA PRUEBA ILÍCITA EN MATERIA PENAL - Salinas Livisaca, Fanny Elizabeth (2016)
At some times to the present case law of some countries like ours have rejected the evidence prohibited and illegal evidence unconstitutional test, mainly under the grounds that by not being prohibited by the rule, is permitted without prejudice to the sanction criminal or administrative person responsible for the violation of fundamental rights. And being one of the most complex evidentiary issues raised at present the wrongfulness and the prohibition of the tests used in the various criminal proceedings, is that this is a very broad terminology used for the doctrine both as for jurisprudence and is usually very uniform often used terms or use; trial or evidentiary prohibitions, prohibited, illegal or illegally obtained evidence, evidence unconstitutional, null test, improper testing, test flawed, irregular or clandestine test. Taking into account the Constitution and the various legal bodies do an assessment of what the person has had many definitions on the subject of study in each of the areas to be treated, I start to say that within the right every human being has rights and obligations. In what follows that every man is subject to the right with ability to claim rights and obligations but with the obligation to answer for their actions. This research work seeks to determine whether the due process is respected not infringe it and whether or evidentiary exclusions test for prohibited and illegal evidence in criminal matters are made. Being the main problem in our environment due process, in a general way, is not respected when presented as evidence, proof prohibited or unlawful since no valuation is argued duly.